2018
DOI: 10.1016/j.athoracsur.2018.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Need for Permanent Pacemaker After Surgical Aortic Valve Replacement Reduces Long-Term Survival

Abstract: The need for PPM after aortic valve replacement independently reduces long-term survival. The rate of PPM placement after surgical aortic valve replacement remains very low but dramatically increases resource utilization. As transcatheter aortic valve replacement expands to low-risk patients, the impact of PPM placement on long-term survival warrants close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 35 publications
3
49
0
5
Order By: Relevance
“…Several previous studies have shown increased preoperative risk/comorbidities and rate of postoperative complications in patients requiring permanent pacemaker after SAVR [23,24] . We found that pacemaker implantation reduces the risk of IHM after mechanical SAVR.…”
Section: Resultsmentioning
confidence: 96%
“…Several previous studies have shown increased preoperative risk/comorbidities and rate of postoperative complications in patients requiring permanent pacemaker after SAVR [23,24] . We found that pacemaker implantation reduces the risk of IHM after mechanical SAVR.…”
Section: Resultsmentioning
confidence: 96%
“…There was no significant difference in permanent pacemaker implantation (PPI) rates between the two valve types. However, the overall PPI rates of 8.22% were high compared to the expected rates following surgical aortic valve replacement, which is 1.9-2.7% (32)(33)(34)(35). Pacemaker implantation rate is an important performance indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Pacemaker implantation rate is an important performance indicator. Patients who require PPI after aortic valve replacement have reduced risk-adjusted long-term survival compared those who do not require pacemaker implantation (35,36). Implantation technique has been shown to be an important factor that can impact pacemaker implantation rates, particularly with regards to the Perceval valve.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in the aging population and recent advances in surgical and transcatheter intervention, many patients who underwent permanent PM implantation had atrial fibrillation and a history of valve procedure. Conduction abnormality requiring permanent PM implantation are frequent and associated with an increased risk of heart failure-related hospitalization and lack of functional improvement and reverse remodeling after either transcatheter or surgical aortic valve implantation [19][20][21]. Data regarding the prognostic impact of PM implantation after valve intervention are somewhat controversial.…”
Section: Plos Onementioning
confidence: 99%